Menjadi Solider Seturut Etika Ironis Liberal Richard Rorty - Agustinus Tamtama Putra (Forum, 2022)
This paper describes contextual ethical views in life as far as humans. The enforcement of justice demands term and conditions that allow its realization. Richard Rorty's idea of an ironic liberal ethic may become an embryo that can structure and shape justice as part of solidarity. The ethic of ironic liberal guides a person not to absolute his views, but to be open to the truth from others. Freedom is upheld as long as it does not cause cruelty to others because cruelty is the worst thing a human being can do. The open and free attitude that is the spirit of the liberal ironist is at odds with the metaphysics. The metaphysics are still looking for a basis for ethical conduct, while the liberal ironists believe that these various foundations are the root of all cruelty in society. By being ironically liberal, of course one becomes just by itself.